Contribution to the knowledge of Mazureus Gomy, 1991 from tropical and equatorial Africa (Coleoptera, Histeridae, Abraeinae) - (:unkn) unknown (My University, 2020)
Description of Chaetabraeus (Mazureus) delajouxi n. sp. and of Chaetabraeus (Mazureus) lejeunei n. sp. of tropical and equatorial Africa. Study of Mazureus Gomy, 1991 of Transvaal Museum of Natural History of Pretoria (Republic of South Africa), the Naturalis Biodiversity Center of Leiden (Netherlands), the Royal Museum of Central Africa of Tervuren (Belgium) and some private collections.
Keywords: African Research